ANALISIS STRUKTUR PEREKONOMIAN DAN PERTUMBUHAN EKONOMI DI KABUPATEN BANYUMAS - Liem, Yohanes (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Economic growth is the process of changing the condition of a country continuously towards the better during a period of time. The existence of economic growth is an indication of the success of economic development. The objective of this research is to find out the contribution to the development of pre-economic structures and economic growth in Banyumas district in 2021 and 2022, to know which sectors are the basis and non-base sectors in the economic structure development and growth of Banyumas district, to know the changes in the superior sector in the structure of the economy of Banyumas District. This research uses secondary data such as Gross Regional Domestic Product (GDP) data, and the rate of economic growth of Banyumas district. The analysis method used is Location Quotient (LQ), Shift Share (SS). From the results of the analysis of the calculation of the LQ sectors that have a value of LQ > 1 i.e. the sector of Processing, Construction, and Procurement of Electricity and Gas, and the sector that has a LQ < 1 i.e. agriculture, Forestry and Fisheries, Mining and Demolition, as well as Information and Communications, from the result of the shift share (SS) indicated that pointing out that there are some sectors that have the potential to be positive